Determination of Auditor Objectivity: An Empirical Study of KAP in The Provinces of Jawa Timur, Jawa Tengah, and DIY - Milatina Laksmita Dewi (Universitas Pamulang, 2025)
This study aims to analyze the factors influencing auditor objectivity in Public Accounting Firms (KAP) in the provinces of East Java, Central Java, and the Special Region of Yogyakarta (DIY). The independent variables in this study include competence, ethical culture, and audit team norms, while auditor objectivity serves as the dependent variable. This study uses a quantitative approach with a survey method through the distribution of questionnaires to 121 auditors working at KAP in the study area. This study uses multiple linear regression tests with the SPSS version 23 program. The results of the study indicate that competence has a positive and significant effect on auditor objectivity. Ethical culture is also proven to have a positive and significant effect on auditor objectivity. In addition, audit team norms have a positive and significant effect on increasing auditor objectivity. These findings indicate that auditors with a good level of competence, working in an environment that implements an ethical culture, and being on an audit team with strong norms will have a higher level of objectivity in carrying out their professional duties. This research is expected to be a consideration for KAP in strengthening audit quality by improving auditor competence, implementing an ethical culture, and strengthening audit team work norms.